Surah An-Nisa Ayat 6-7, 12, 176 Defenisi Tentang warisan - Ishaq, Ishaq (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2024)
Inheritance is the transfer of rights and obligations from the testator to his heirs based on applicable legal provisions. Inheritance does not only include property rights, but also includes all kinds of other rights and obligations that can be valued in money and left by the testator at the time of his death. This transfer process occurs automatically when the testator dies and is mandatory, the purpose of this study is to know and understand about Inheritance, to know and understand about the Interpretation of Surah An-Nisa Verses 6-7, Annisa Verse 12 and Annisa verse 176